A re-examination of the exchange rate – interest rate differential relationship in Ghana - Isaac Kwesi Ofori; Mark Kojo Armah (ZBW - Leibniz Information Centre for Economics, 2021)
This paper revisits the exchange rate and interest rate differential relationship since Ghana adopted the inflation targeting regime. Using macro-data spanning 2002 to 2019 for Ghana and the United States, we show the nonexistence of the relationship in both the short-run and long-run. Further, we show a positive but slow responsiveness of exchange rate to interest rate differential shocks from the short-run to medium term. The long-run result however shows a case of a strong and significant response of exchange rate to interest rate differential shocks. We recommend that the Bank of Ghana address perennial macroeconomic instability, especially on inflation which we conjecture to fuel investment uncertainty and investment insensitivity to the interest rate.
Keywords: A1; E4; E43; E3; F5; 330; Inflation Targeting; Exchange Rate; Impulse Response Function; Interest Rate Differential; VAR; Ghana